2022
DOI: 10.7759/cureus.32215
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Gastric Mucormycosis in a 21-Year-Old Patient With Hemophagocytic Lymphohistiocytosis

Abstract: Mucormycosis is an angioinvasive, opportunistic infection. Diabetes Mellitus and immunosuppression are the most common risk factors for fungal infection. Without prompt treatment, the infection can be fatal. A 21-year-old male patient presented with gastritis-like symptoms refractory to proton pump inhibitor (PPI) therapy. He recently received treatment for Hemophagocytic Lymphohistiocytosis (HLH), confirmed by bone marrow biopsy and fungal sinusitis. Esophagogastroduodenoscopy (EGD) revealed extensive gastric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In a clinical study, 12 (60%) of the 20 pediatric HLH patients died, with eight deaths attributed to invasive infections including disseminated cytomegalovirus infection (1/20), enterobacterial sepsis (1/20), and invasive fungal infections (6/20) [ 17 ]. A recent case report reported a 21-year-old male patient on HLH treatment who presented with proton pump inhibitor (PPI)-refractory gastritis-like symptoms and subsequent gastroscopy suggestive of gastric trichomycosis, after which the patient was treated with antifungal drugs and the necrotic gastric tissue was removed [ 18 ]. The paucity of studies of complex infections in HLH may be related to the fact that infection is a secondary cause of HLH, and current reports have focused on infection as a cause of secondary HLH.…”
Section: Current Status Of Complex Infections In Hlhmentioning
confidence: 99%
“…In a clinical study, 12 (60%) of the 20 pediatric HLH patients died, with eight deaths attributed to invasive infections including disseminated cytomegalovirus infection (1/20), enterobacterial sepsis (1/20), and invasive fungal infections (6/20) [ 17 ]. A recent case report reported a 21-year-old male patient on HLH treatment who presented with proton pump inhibitor (PPI)-refractory gastritis-like symptoms and subsequent gastroscopy suggestive of gastric trichomycosis, after which the patient was treated with antifungal drugs and the necrotic gastric tissue was removed [ 18 ]. The paucity of studies of complex infections in HLH may be related to the fact that infection is a secondary cause of HLH, and current reports have focused on infection as a cause of secondary HLH.…”
Section: Current Status Of Complex Infections In Hlhmentioning
confidence: 99%
“… 7 The authors stressed the mortality being up to 85% without early diagnosis and therapy. 7 Noor et al 10 reported a 21-year-old man presenting gastritis-like symptoms, who was recently treated for hemophagocytic lymphohistiocytosis, and a fungal sinusitis. The upper GI endoscopy revealed an extensive gastric involvement by mucormycosis, and the patient underwent antifungal drugs and resection of the necrotic gastric tissue.…”
mentioning
confidence: 99%
“…The authors highlighted the role of early diagnosis and prompt treatment on outcome. 10 Yuvaraj et al 12 described a 53-year-old man with diabetes mellitus and alcoholism who had acute abdominal pain and hematemesis. The imaging studies showed a gastric wall thickening and exophytic ulceration involving the greater curvature and the splenic hilum, and evidence of splenic infarction.…”
mentioning
confidence: 99%